Physical and numerical modelling of air-water flows: An Introductory Overview. (September 2021) - Gualtieri, C.; Chanson, H.
Abstract: In free-surface turbulent flows, large amount of air may be entrapped and advected in the water current. The resulting air-water flows are frequently observed in natural water systems, where they are also relevant to water quality, ecological sustainability and integrated assessment within such systems. Herein, a review of physical and numerical modelling of air-water flows is developed, providing some fundamentals towards a consistent modelling of such flows to graduate and Ph.D. level students as well as young researchers in environmental sciences and engineering, with pre-requisite knowledge in basic fluid mechanics. After some theoretical and metrology considerations, the main criteria for the design of physical models and the current literature on the numerical studies are discussed. Two case-studies, the hydraulic jump and the dropshaft, are used to show the application of such criteria and methods. Overall, the paper presents current knowledges/challenges on physical and numerical modelling of self-aerated free-surface flows. Highlights: Fundamentals towards a consistent modelling of self-aerated flows are provided. The main criteria for the design of physical models as well as the current literature on the numerical studies are discussed. Aimed to graduate and Ph.D. students as well as young researchers in environmental sciences and engineering.